Strategi Pengembangan Wakaf Produktif untuk Kesejahteraan Umat - Anisa Fitria Utami (ISLAMICONOMIC: Jurnal Ekonomi Islam, 2019)
Abstract. The Strategy Of Productive Waqf Management For General Welfare (Case Study On Nadzir Of Malang Islamic University Foundation). The purpose of this research is to find out the strategy of productive waqf management for general welfare that conducted by The Nadzir of Universitas Islam Malang Foundation. Malang City still has a quite high poverty rate that is 4,6%. Waqf is an instrumen in islamic economy that can solve poverty beside zakat. The development of waqf in Malang City is increased every year plus there are many waqf asset that spreaded in all sub-district in Malang City. The Nadzir of Universitas Islam Malang Foundation that domiciled in Malang City was given funds by Kementrian Agama with waqf fund agreement. The purpose of that waqf fund is as the example on productive waqf management. The Nadzir of Universitas Islam Malang Foundation has succeed in developing eleven VIP Rooms in UNISMA Hospital. 70% from the outcomes of that management, are used to development and management of the VIP Rooms and used to develop a minimarket that spreaded in several regions. 20% from the outcomes of productive waqf management was channeled to the 40 mauquf alaih periodically. Abstrak. Strategi Pengelolaan Wakaf Produktif untuk Kesejahteraan Umat (Studi Kasus di Nadzir Yayasan Universitas Islam Malang). Penelitian ini bertujuan untuk mengetahui strategi pengelolaan wakaf produktif untuk kesejahteraan umat yang dilakukan oleh Nadzir Yayasan Universitas Islam Malang. Kota Malang masih memiliki tingkat kemiskinan yang cukup tinggi yaitu sebesar 4,6 %. Wakaf merupakan salah satu instrumen dalam ekonomi islam yang mampu mengatasi kemiskinan selain zakat. Perkembangan wakaf di Kota Malang semakin meningkat tiap tahunnya ditambah banyak aset wakaf yang tersebar di seluruh kecamatan di Kota Malang. Nadzir Yayasan Universitas Islam Malang yang berkedudukan di Kota Malang diberi dana oleh Kementrian Agama dengan akad dana wakaf. Tujuan dari dana wakaf tersebut adalah sebagai percontohan dalam pengelolaan wakaf secara produktif. Nadzir Yayasan Universitas Islam Malang telah berhasil membangun Ruang VIP di Rumah Sakit UNISMA sebanyak 11 kamar, 70% dari hasil pengelolaan tersebut digunakan untuk pengembangan dan pengelolaan Ruang VIP serta digunakan untuk membangun minimarket yang tersebar di beberapa daerah. 20% hasil pengelolaan wakaf produktif disalurkan kepada sekitar 40 mauquf alaih secara periodik.